LEO satellite active FTC with aerodynamic disturbance decoupled fault diagnosis. (January 2020) - Castaldi, Paolo; Mimmo, Nicola; Simani, Silvio
Abstract: This paper presents an attitude active fault tolerant control for a satellite simulated model. The proposed fault tolerant controller consists of two main parts: a nominal controller, designed assuming that the system is healthy, and a fault diagnosis module which aims at detecting, isolating and estimating the fault affecting the system. The fault diagnosis module is designed by using the non-linear geometric approach tool which allows to obtain detection residuals and estimation filter decoupled from the aerodynamic disturbance representing the main uncertainty in low Earth orbits. The simulation results show the advantages, in terms of attitude tracking accuracy, obtainable when implementing the proposed method.